2017
DOI: 10.9734/bjesbs/2017/34012
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Learning Cycle Models on Nigerian Senior Secondary Students’ Anxiety towards Chemistry

Abstract: Aims: The method of teaching Chemistry in Nigerian classrooms has given it an image of being a subject with a body of abstract ideas, giving room for manifestation of anxiety towards the subject at the secondary school level. It is within this context that this study investigated the impact of 5E and PDEODE Learning Models on students' anxiety towards senior secondary Chemistry. Study Design: Quasi experimental pre-test-post-test-control group design was used by the researchers to carry out the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Despite the importance of Basic Science to a country's progress and socioeconomic development, students' interest and proficiency in the subject is waning in Nigerian classrooms. Several researches have shown that Nigerian science classrooms are compounded with lot of challenges; prominent among which are poor teaching strategies adopted by teachers [7,8]; students' lack of interest in the sciences [9]; gender [10]; availability and usability of science laboratory equipment's [11]; students' anxiety [12]; students' self-efficacy [13] and the abstract nature of science [14].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of Basic Science to a country's progress and socioeconomic development, students' interest and proficiency in the subject is waning in Nigerian classrooms. Several researches have shown that Nigerian science classrooms are compounded with lot of challenges; prominent among which are poor teaching strategies adopted by teachers [7,8]; students' lack of interest in the sciences [9]; gender [10]; availability and usability of science laboratory equipment's [11]; students' anxiety [12]; students' self-efficacy [13] and the abstract nature of science [14].…”
Section: Introductionmentioning
confidence: 99%